An Exploration of the Link Between Masculinity and Endorsement of IPV Myths in American Men - Gage, Alida Novarese (Journal of interpersonal violence, 2021)
Current research has established a connection between men’s endorsement of traditional masculinity ideology and their perpetration of intimate partner violence (IPV) toward women. However, research has not yet identified the cognitive and affective pathways that link the endorsement of masculinity ideology and men’s beliefs about IPV. The current study examined men’s fear of intimacy, ambivalent (i.e., hostile and benevolent) sexism, and relationship dominance as potential mediating factors of the relationship between endorsement of traditional masculinity ideology and the acceptance of myths about male-to-female IPV in a community sample of 101 American men. Results supported the hypothesized relationship between men’s endorsement of traditional masculinity ideology and their support of myths minimizing the impact of male-to-female IPV or shifting the perceived responsibility for the offenses from the male perpetrators to the female victims. Multiple regression analyses indicated that while men’s hostile sexism and a preference for dominance in relationships did partially mediate the proposed relationship, fear of intimacy did not. The sample was largely homogeneous in terms of race/ethnicity, socioeconomic status, and educational background, although heterogeneous in age. Implications for prevention of IPV include the importance of addressing and challenging the pervasiveness of societal support of IPV myths. Clinical implications include the need for male-centric therapeutic interventions that respect male viewpoints, struggles, and strengths, and that work with, rather than against, a client’s sense of masculinity.